Adsorption of Acid violet-17 from Synthetic aqueous Solution on Two kinds of Cucumis sativus L. Peel adsorbent - Smitha T.; Santhi T. (International Journal of Research in Chemistry and Environment (IJRCE), 2015)
The use of low-cost and eco-friendly adsorbents has been investigated as an ideal alternative to the current expensive methods of removing dyes from waste water. The peel of Cucumis sativus L. was collected from the locale and converted into low cost adsorbents. An acid dye, Acid violet 17 has been used as the adsorbate. Adsorption data were modeled using Langmuir, Freundlich, Temkin and Dubinin-Radushkevich adsorption isotherms.